2013
DOI: 10.4172/2161-1122.1000157
|View full text |Cite
|
Sign up to set email alerts
|

Stress and its relief among undergraduate dental students in a tertiary health care centre in eastern Nepal

Abstract: Background: Dentistry is associated with a number of stressors resulting to depression, anxiety, substance misuse, absenteeism, diminished work efficiency, and burnout. The study was conducted with the objectives to know the prevalence and type of stressors; their consequences stress relievers among the clinical dental students. Methods:It is a descriptive cross-sectional quali tative study carried out using a self-administered questionnaire among the clinical dental students of a college of dental surgery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 17 publications
2
28
2
Order By: Relevance
“…This high response rate is probably due to high individual perception of stress by students thus feeling the need to be actively involved in its identification and management. Results from this study further support available evidence that health professional students are stressed (Sabita Paudel et al., ; Saipanish, ; Salam et al., ). In this study, more than half (57.4%) of the respondents were stressed.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This high response rate is probably due to high individual perception of stress by students thus feeling the need to be actively involved in its identification and management. Results from this study further support available evidence that health professional students are stressed (Sabita Paudel et al., ; Saipanish, ; Salam et al., ). In this study, more than half (57.4%) of the respondents were stressed.…”
Section: Discussionsupporting
confidence: 87%
“…Basing on available evidence, it is not surprising that in this present study we found high prevalence rate (57.4%) among health professional students at Makerere University. It is reported that health professional students are stressed more than students from other faculties (Aktekin et al., ) and this stress affects not only their physical but also mental well‐being (Danz et al., ; Dyrbye, Thomas, & Shanafelt, ; Paudel et al., ) which ultimately may affect patient care in future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stressors associated with dentistry include time and scheduling pressures, managing uncooperative patients and the highly technical and intensive nature of work. 3 Chronic occupational stress of such kind can result in professional burnout, anxiety and depression. Professional burnout has potent adverse effect.…”
Section: Introductionmentioning
confidence: 99%